Offshore Wind Transmission and Grid Interconnection across U.S. Northeast Markets - Smith, Kelly; Lenney, Samuel; Marsden, Oliver; Kates-Garnick, Barbara; Stanković, Aleksandar; Hines, Eric (Tufts University. Tisch Library., 2021)
Executive Summary; This report introduces the staggering growth in the U.S. offshore wind industry to date and maps this growth onto the capacity of existing land-based transmission grids on the U.S. Atlantic Coast. Focusing specifically on available coastal points of interconnection (POIs), the report demonstrates that the U.S. offshore wind industry will quickly encounter limits to build-out capacity if interregional efforts to coordinate land-based transmission upgrades and maximize POI effectiveness are not engaged immediately. The report advocates for strong engagement between the U.S. Federal Government, States, and Regional Transmission Organizations (RTOs) It also recommends the immediate development of Transmission Expansion Planning (TEP) efforts that consider the future grid as a whole as a means to improving near-term, state-level offshore wind power and transmission procurements. Without clear plans for the grid of the future, there can be no energy transition. We hope this report will be helpful to readers with all levels of expertise in the energy transition, the electricity grid, and the offshore wind industry.; Offshore Power Research & Education Collaborative Report Number OSPRE-2021-01.